The Levels of Visual Distinction of Color Design Systems among Users of Educational Interior Spaces - halaf, Khalaf (International Journal of Psychosocial Rehabilitation, 2020)
The research covered the study of the visual distinction of the Color Design Systems among the users of the educational interior spaces. The research problem and target was defined in defining the levels of the visual distinction among the fine arts college students in Diyala University (Plastic Art Department, Arts Education Department). The research also defines the more visually distinct color system among the users of the educational interior spaces. Then, comes identifying the designing features of the color system which are distinguishable for most users of the educational interior spaces. During this study, a tool to measure the levels of the color distinguishable visual levels. This tool is applied on the sample of users of the educational interior levels; which is followed by implementing this tool on the sample from users of the educational interior spaces (Schools Halls) in Diyala University – College of Fine Arts in the Academic, Year (2018-2019). This sample consisted of 130 male & female & students of users of the interior spaces. This research reached a group of results including there are statistical significant differences between the visual distinction and between the male & female students and between the plastic arts department students and the arts education department and in favor of plastic arts students department. The Conclusions showed the possibility of using the research tool to measure the level of the color visual distinction for the fine arts college students in the Iraqi Universities through distinguishing the color systems for the educational interior spaces.